Ekspertiza 93 . Ekspertiza 93 . Examination '93 . Экспертиза 93 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion about the arrangement of political forces in Russia. Featured in the program: Novodvorskaia, Valeriia Il'inichna (Human Rights Activist); IAkovlev, Aleksandr Nikolaevich (Politician); Anpilov, Viktor Ivanovich (Politician); Dol'skii, Aleksandr (Poet); Goriachev, Mark (Entrepreneur) Contributors: Polianskaia, Anna (Anchor) Дискуссия о расстановке политических сил в России. В программе участвуют: Новодворская, Валерия Ильинична (Правозащитник); Яковлев, Александр Николаевич (Политик); Анпилов, Виктор Иванович (Политик); Дольский, Александр (Поэт); Горячев, Марк (Предприниматель ) Создатели: Полянская, Анна (Ведущий/Ведущая)